The role of new media in the political participation of young people in Kazakhstan - Tolen, Ж.М.; Alisherova, А.Б. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2023)
In this article the participation of young people in the political life of Kazakhstan and the role of new media will be examined. The theoretical and conceptual significance of political participation and social networks is discussed. The aim of the research is to contribute to the debate in this area by exploring how new media contribute to the participation of young people in political life. As a hypothesis of the work, the concept was adopted, according to which «new media contribute to the increase of political participation and activity of young people.» Based on the research work of the youth of Kazakhstan and Russia on the use of social networks, the analysis of the political participation of young people and the interaction of new media is carried out. A comparative analysis of the activity of the political participation of the youth of Russia and Kazakhstan is carried out, the features of the political participation of the youth of Kazakhstan are revealed. It has been found that the three most frequently used social networks among the youth of these two countries are Vkontakte, Instagram, and YouTube. In order to study the specifics of online and offline participation, a case study is conducted. The analysis of the political events that took place in Kazakhstan and Russia is carried out, in particular the large protests in support of Alexei Navalny in Russia and the events of“«Qandy Qantar”« in Kazakhstan. Based on the results of a comparative analysis, the study has revealed the level of interest of young people in Kazakhstan in politics. As a result, it is concluded that currently young people receive political information through social networks. It is concluded that in the future Kazakhstan has the potential for the development of political and civic activity of young people in social networks.